Fungsionalisasi ADR dan Penyelesaian Sengketa Lingkungan Hidup - R F Saragih (Fakultas Hukum Universitas Islam Indonesia, 2000)
The resolution of the environmental disputes on the Act No. 23,1967 of the Environmental Management is usually conducted by two ways: incourt and outside court. Since, as widely known, the settlement of the disputes in court is often belated, the settlement outside court is an alternative to anticipate the betatedness, it is often known as theAlternative Dispute Resolution (ADR). Based on this argument, an attempt to function the ADR in the environmental dispute resolution becomes urgently required, primarily interms of the environmental disputes in civil cases.